Pengaruh Bagian Organ dan Persentase Ekstrak Tanaman Kayu Putih (Melaleuca leucadendra L.) terhadap Perkecambahan Benih Jagung (Zea mays) dengan Metode Bioassay - Syprianus Ceunfin (Fakultas Pertanian, Universitas Timor, 2019)
Maize production has recently declined. This is as a result of shifting the utilization of productive lands into unproductive lands. Therefore, intercropping becomes one of alternative food production. The most potential land for growing food crops is the kayu putih based production forest. This study aims to determine the effect of organ parts and the percentage of kayu putih extracts on germination of maize seeds by bioassay method and determine the level of germination level resistance to allelopathy. The study was conducted in March-May 2015 in Bangun Tapan, Bantul, Yogyakarta. The design used in this research is Completely Randomized Design (CRD) Factorial. The first factor is the parts of the plant organ (E) used as the extract, consisting of 9 levels, namely: root 1 zone extract, 2 zone root extract, bark extract, fresh leaf extract, leaf litter extract, root 1 zone extract + bark extract + extract fresh leaf + litter extract, 2 zone root extract + bark extender + fresh leaf extract + litter extract, bark extract + fresh leaf extract + litter extract, fresh leaf extract + leaf litter extract and a second factor is an extract concentration of 6 levels i.e control, 20 % extract, 40 % extract, 60 % extract, 80 % extract, 100 % extract with 10 mL size. There are 54 treatment combinations each repeated 3 times so the total research unit is 162 trays. Variable observation in this research is counting seed vigor and stress tolerance index on seed vigor. Research results indicates that there is no interaction between part treatment and percentage of kayu putih extract to germination of maize seeds, all parts of fresh organs of kayu putih plants at various concentrations are able to inhibit the growth and development of sprouts and put the maize sprouts at moderate level until susceptible in grouping stress tolerans index.